Prolonged erythrocyte auto-incubation as an alternative model for oxidant generation system - da Silva, Danilo Grünig Humberto [UNESP]; Chaves, Nayara Alves [UNESP]; Miyamoto, Sayuri; de Almeida, Eduardo Alves (Elsevier, 2019)
This study investigated the effects of incubation period and melatonin treatment on red blood cell (RBC) metabolism in an auto-incubation model of H 2 O 2 -induced oxidative stress. The study was carried out on three healthy adult donors by incubating RBCs in their own plasma at 37 °C, or under the influence of 1 mM H 2 O 2 with and without 100 μM melatonin at different times (0, 1, 3 and 6 h). We assessed incubation period, treatment, as well as any interaction effects between these predictors on erythrocyte osmoregulation, hemolytic rate, oxidative stress markers, and adenylate nucleotide levels. We did not find any relevant effects of both incubation period and treatments on osmotic, antioxidant and adenylate parameters. On the other hand, hemolysis degree and biomolecule oxidation levels in the plasma increased over time, 3-fold and about 25%, respectively, regardless any treatment influence. H 2 O 2 treatment more than doubled protein carbonyl groups, regardless time in plasma, and in a time-depending way in erythrocyte membrane extract, effects that were neutralized by melatonin treatment. Through multivariate analyses, we could expand the understanding of energy and redox metabolisms in the maintenance of cellular integrity and metabolic homeostasis. Another interesting observation was the 65–75% contribution of the oxidative lesion markers on hemolysis. Hence, these findings suggested a new and more intuitive RBC suspension model and reinforced the beneficial use of melatonin in human disorders.
Keywords: Antioxidants; Erythrocyte metabolism, oxidative stress; Hydrogen peroxide; Melatonin